Functional adaptation of glial cells at neuromuscular junctions in response to injury. Issue 9 (27th April 2022) - Perez‐Gonzalez, Anna P.; Provost, Frédéric; Rousse, Isabelle; Piovesana, Roberta; Benzina, Ouafa; Darabid, Houssam; Lamoureux, Benoit; Wang, Yu Shi; Arbour, Danielle; Robitaille, Richard
Abstract: Synaptic elements from neuromuscular junctions (NMJs) undergo massive morphological and functional changes upon nerve injury. While morphological changes of NMJ‐associated glia in response to injury has been investigated, their functional properties remain elusive. Perisynaptic Schwann cells (PSCs), glial cells at the NMJ, are essential for NMJ maintenance and repair, and are involved in synaptic efficacy and plasticity. Importantly, these functions are regulated by PSCs ability to detect synaptic transmission through, notably, muscarinic (mAChRs) and purinergic receptors' activation. Using Ca 2+ imaging and electrophysiological recordings of synaptic transmission at the mouse NMJ, we investigated PSC receptors activation following denervation and during reinnervation in adults and at denervated NMJs in an ALS mouse model (SOD1 G37R ). We observed reduced PSCs mAChR‐mediated Ca 2+ responses at denervated and reinnervating NMJs. Importantly, PSC phenotypes during denervation and reinnervation were distinct than the one observed during NMJ maturation. At denervated NMJs, exogenous activation of mAChRs greatly diminished galectin‐3 expression, a glial marker of phagocytosis. PSCs Ca 2+ responses at reinnervating NMJs did not correlate with the number of innervating axons or process extensions. Interestingly, we observed an extended period of reduced PSC mAChRs activation after the injury (up to 60 days), suggesting a glial memory of injury. PSCs associated with denervated NMJs in an ALS model (SOD1 G37R mice) did not show any muscarinic adaptation, a phenotype incompatible with NMJ repair. Understanding functional mechanisms that underlie this glial response to injury may contribute to favor complete NMJ and motor recovery. Main Points: Reduced perisynaptic Schwann cells (PSC) muscarinic receptors activation at denervated and reinnervating neuromuscular junctions. mAChRs regulate PSCs gene expression of the phagocytic marker galectin‐3. A delay to return to normal reveals a glial memory of injury.